Identification of Sustainable Supply Chain Performance in Primary Cocoa Processing (Case Study in Patuk, Yogyakarta) - Khairani Tasyarafa Shelia; Kurniawan Muhammad Prasetya; Widodo Kuncoro Harto; Marwati Tri; Djaafar Titiek Farianti (BIO Web of Conferences, 2023)
This study identified the handling of dry fermented cocoa bean production, analyzed the level of cocoa supply chain (SC) performance in Patuk, and developed recommendations for poor performance to improve SC performance. In this study, environmentally friendly handling was carried out by observing the SC and processing process, and SC performance was measured based on the Supply Chain Operations Reference (SCOR) model in the scope of reliability, responsiveness, and agility supported by the 2.2 Analytical Hierarchy Process (AHP) weighting method using pairwise comparison. The result of this study indicates that sustainable practices from the seeding, nurturing, harvesting, and shipping stages are easier to implement due to the small scale and proximity to residential areas and processing units. Cocoa SC performance in Patuk is divided into 3 parts, namely for farmer performance (79.79), collective traders (70.23), and processing industry (83.29). Improvements that can be made to improve the performance of the SC are by increasing plant maintenance, recording production, and making contracts. The benefits of this study are to encourage the adoption of environmentally friendly cocoa cultivation and processing practices, provide information on SC factors on SC performance, and provide recommendations for performance improvement.